RpoS-Dependent Transcriptional Control of sprE: Regulatory Feedback Loop - Ruiz, Natividad (American Society for Microbiology, 2001)
The stationary-phase response exhibited by Escherichia coli upon nutrient starvation is mainly induced by a decrease of the ClpXP-dependent degradation of the alternate primary ς factor RpoS. Although it is known that the specific regulation of this proteolysis is exercised by the orphan response regulator SprE, it remains unclear how SprE's activity is regulated in vivo. Previous studies have demonstrated that the cellular content of SprE itself is paradoxically increased in stationary-phase cells in an RpoS-dependent fashion. We show here that this RpoS-dependent upregulation of SprE levels is due to increased transcription. Furthermore, we demonstrate that sprE is part of the two-gene rssA-sprE operon, but it can also be transcribed from an additional RpoS-dependent promoter located in the rssA-sprE intergenic region. In addition, by using an in-frame deletion in rssA we found that RssA does not regulate either SprE or RpoS under the conditions tested.